SOCIAL REPRESENTATIONS ABOUT HEALTH (Fiep Bulletin - online, 2012)
It is a qualitative study that aims to identify the social representations on health produced by the elderly in a sample of 240 elderly of both sexes, living in the city of João Pessoa. For collection held an interview with the Test of Free Association of Words with the inductive stimulus 'health'. The data collected from the responses evoked by the elderly were organized to build a dictionary of words adjectives concerning the stimulus / inducer and sumetidos the semantic analysis with the help of software Alceste. The results show similarities and differences in social representations of the old from the variables: the elderly describe health and aging with content less negative although there was also content neutral. For Two (1991), the interest in finding convergences can be explained by them as a reference work that will absorb the news and controversies arising out of what happens in the real world.
Keywords: Health; Social representations; Elderly.